2015
DOI: 10.1590/s0100-83582015000300013
|View full text |Cite
|
Sign up to set email alerts
|

Annual Grasses Control With Topramezone in Mixture With Als-Inhibiting Herbicides

Abstract: Panicoid grasses are major weeds of maize and sugarcane as well as of several other important grains, including sorghum, pearl millet, and foxtail millet. Pot trials were conducted to study the activity and potential interactions of topramezone in mixture with recommended rates of rimsulfuron or nicosulfuron on three annual panicoid grasses (i.e. Echinochloa oryzoides,E.phyllopogon, and Panicum miliaceum). Target weeds were treated at the four- to five-leaf growth stage. On the basis of fresh weight reduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…49 Similar outcomes have been observed in various studies. 46,53,54 This observation is in accordance with the finding of Zhang et al(1995). 22 On the other hand, several mixtures resulted in synergistic interactions in dicots.…”
Section: Weed Lifespansupporting
confidence: 88%
See 2 more Smart Citations
“…49 Similar outcomes have been observed in various studies. 46,53,54 This observation is in accordance with the finding of Zhang et al(1995). 22 On the other hand, several mixtures resulted in synergistic interactions in dicots.…”
Section: Weed Lifespansupporting
confidence: 88%
“…For example, when applied on Echinochloa crus-gall , mixtures of fenoxaprop and bensulfuron, carfentrazone, halosulfuron, triclopyr, or bentazon have resulted in additivity, the most dominant interaction in monocots, and antagonistic interaction . Similar outcomes have been observed in various studies. ,, This observation is in accordance with the finding of Zhang et al(1995) . On the other hand, several mixtures resulted in synergistic interactions in dicots. ,, However, unwanted interactions were observed in dicots.…”
Section: Impact Of Weed-based Factors On Herbicide Interactionssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to this non-chemical strategy of crop rotation, for johnsongrass control, ALS inhibiting herbicides such as rimsulfuron at 10 g ha -1 have been found very effective (Damalas and Eleftherohorinos, 2001). However, contrary to HPPD herbicides and atrazine synergistic combination responses, many researchers (Damalas and Eleftherohorinos, 2001;Kaastra et al 2008;Damalas et al 2015) have reported two way antagonistic interactions between HPPD and ALS inhibiting herbicides, which are weed species specific. While, Schuster et al (2008) showed the decreased efficacy of sulfonylurea herbicides (nicosulfuron and foramsulfuron) on Harlan} with the addition of mesotrione to sulfonylurea herbicides.…”
Section: Johnsongrass (S Halepense) Infestation As Affected By Crop mentioning
confidence: 99%
“…These factors make it difficult to predict herbicide persistence. Agro-chemical companies sometimes make combinations of herbicides, especially the selective ones so that they more effectively deal with a wide range of weed problems faced by farmers (Damalas et al, 2015). Stellar Star, active ingredients Topramezone (pyrazolone) and Dicamba (benzoic acid compound) is one such herbicide which is recommended for weed control under smallholder farming conditions.…”
Section: Introductionmentioning
confidence: 99%